Ketahanan pantai terhadap bahaya banjir dan erosi: Studi komparasi Portsmouth (Inggris) dan Semarang (Indonesia) - Saleha, Saleha; Koestoer, Raldi Hendro; Lukijanto, Lukijanto (Universitas Riau, 2022)
Tidal flood and erosion are familiar phenomena in coastal areas that have an impact on the destruction of facilities and infrastructure (water, waste management, drainage) as well as environmental damage which is marked by a decrease in the quality of life of the community. However, the community persisted and chose to stay in the area and the population was increasing from year to year. Community resilience can be seen from several aspects: economic, social, infrastructure, and health. Building community resilience depends on social relationships, networks, and connectedness among communities. This paper reviews and compares the level of community resilience in Portsmouth (UK) and Semarang (Indonesia) to the erosion and flood disasters that hit these regions. With the descriptive comparative method, it is studied how the community's resilience to floods and abrasion is studied. The analysis results show that despite adequate defenses, Portsmouth’s resilience faces a higher economic risk of disasters and the resulting residual risks. Changes that occur on the coast of Semarang City have made people have to carry out a learning process to maintain their lives in the context of adaptation to the social, political, economic, and ecological environment in which the population lives.